Appraisal of Nigeria’s Obligation on Adolescents’ Access to Sexual and Reproductive Health Care - Savage-Oyekunle, Oluremi A. (European Scientific Journal, ESJ, 2018)
The positive obligations on states parties to ensure covenant rights will only be fully discharged if individuals are protected by the state, not just against violations of covenant rights by its agents, but also against acts committed by private persons or entities that would impair the enjoyment of covenant rights…. (Paragraph 8 General Comment 31 Human Rights Committee) This article explores the responsibility of the Nigerian state towards ensuring female adolescents’ access to sexual and reproductive health (SRH) care information and services especially contraceptive information and services. It thereafter, considers the stance of the treaty monitoring bodies to state parties’ obligations on the right to access SRH care information and services. The article concludes by declaring the need for judicial activism and stricter monitoring of the government’s activities in other to ensure that adolescents enjoy actual access to SRH care information and services.